Going Forward with #MeToo Movement: Towards a Safer Work Environment. Issue 2 (April 2019) - Gupta, Rajiv; Gupta, Arunima; Nehra, Dharmender
Abstract: Introduction: The volcanic eruption of the #MeToo movement shows that the problem was there for long and was simmering on. The movement was initiated with the aim of knowing the magnitude of the problem and has now spread worldwide. The cases of the Me Too sexual wave are recent and have not yet attracted much scientific attention, though literature on sexual harassment is widely available and the psychological mechanisms implicated in this movement can be understood and examined through it. Objectives: This article aims to attract attention of the medical fraternity to update themselves of this issue which is essential for better understanding of the movement which has potentially good, bad, and ugly undercurrents. We will call attention to these aspects perusing the literature both at national and international levels. This would also be subjected to an analysis of the established concepts and principles of human psychology and behavior. Conclusion: It is amply clear that the time for sweeping things under the carpet is over and the catharsis that flooded the social media, print media, and TV just show how important it is to make the future workplace fair to both genders.